The Influence of Fiscal Rules on the Fiscal Stability in the EU Member States (European Journal of Marketing and Economics, 2024)
Due to the rapid increase of the budget deficit and public debt in many the EU countries after 2008, fiscal policy has faced a significant challenge for developing an appropriate tools to strengthen fiscal discipline and thereby improve the quality of public finance. Institutional mechanisms such as among others numerical fiscal rules play an important role in maintaining the fiscal discipline and support fiscal credibility of the state. Fiscal rules are most often defined as permanent constraints on fiscal policy, expressed by indicators introducing a limit for a particular fiscal aggregate, such as a budget deficit (real or structural), public debt, public expenditure or public revenue. The theoretical objective of the article is to analyze the institutional dimension of numerical fiscal rules (their type, legal basis, transparency, complexity, flexibility, adequacy and coherence). The empirical purpose, on the other hand, is to conduct a statistical analysis and to examine the relationship between the value of the fiscal rules index and the level of budget deficit and public debt in 28 Member States of the European Union. Examining the effectiveness of applied fiscal rules, at both European and national level seems to be the most valuable part of the analysis.
Keywords: fiscal policy, numerical fiscal rules, fiscal rules index, budget deficit, public debt